Application of HepaRG mono- and HepaRG:THP-1 cocultures as immune responsive hepatotoxicity models - Gijs J.J. van Slobbe; Mathias Busch; Wouter Bakker; Coen Govers; Hans Bouwmeester (Toxicology, 2026)

Pro-inflammatory response of human iPSC-derived intestinal epithelial monolayers towards microbial toxins LPS and nigericin - Germaine Aalderink; Hugo Brouwer; Jingxuan Wang; Aafke W. F. Janssen; Meike van der Zande; Coen Govers; Tamara Hoppenbrouwers; Hans Bouwmeester; Mathias Busch (Archives of Toxicology, 2026)
The intestinal epithelium forms a selective barrier between the intestinal lumen and the subepithelial layer. Intestinal epithelium plays a critical role in initiating inflammatory tissue responses in vivo, which remains challenging to emulate in vitro. Caco-2 cells are commonly used models of the intestinal epithelium, but lack crucial receptors and pathways associated with pro-inflammatory reactions. Human-induced pluripotent stem cell (iPSC)-based in vitro models are assumed to provide a system that better emulates in vivo responses. This study evaluated the inflammatory response of iPSC-derived intestinal epithelial cells (IEC) and Caco-2-derived intestinal epithelial cells to the microbial toxins lipopolysaccharide (LPS) and nigericin. Here, iPSCs were differentiated towards enterocyte, goblet- and Paneth-like cells without using three-dimensional culture techniques. The formed monolayer barriers were exposed to a combination of 0–100 µM nigericin and 100 ng/mL LPS on either the apical or basolateral side. The treatment-induced expression of cytokine genes and cytokine secretion were compared between the iPSC-derived cell model and differentiated Caco-2 cell layers. Nigericin exposure in combination with LPS significantly reduced transepithelial electrical resistance in the iPSC-derived model, and resulted in a tenfold increased secretion of the pro-inflammatory cytokines interleukin (IL)-6, IL-8, and tumor necrosis factor-alpha compared to the negative control. A similar increase was observed for the mRNA expression of these cytokines. No significant effect on TEER, cytokine secretion, or mRNA expression was observed in the Caco-2 model. Overall, this study shows that iPSC-IECs are a more sensitive model compared to Caco-2 to emulate inflammatory perturbations of the human intestinal epithelium.